3‐D multiobservable probabilistic inversion for the compositional and thermal structure of the lithosphere and upper mantle: III. Thermochemical tomography in the Western‐Central U.S. Issue 10 (18th October 2016) - Afonso, Juan Carlos; Rawlinson, Nicholas; Yang, Yingjie; Schutt, Derek L.; Jones, Alan G.; Fullea, Javier; Griffin, William L.
Abstract: We apply a novel 3‐D multiobservable probabilistic tomography method that we have recently developed and benchmarked, to directly image the thermochemical structure of the Colorado Plateau and surrounding areas by jointly inverting P wave and S wave teleseismic arrival times, Rayleigh wave dispersion data, Bouguer anomalies, satellite‐derived gravity gradients, geoid height, absolute (local and dynamic) elevation, and surface heat flow data. The temperature and compositional structures recovered by our inversion reveal a high level of correlation between recent basaltic magmatism and zones of high temperature and low Mg# (i.e., refertilized mantle) in the lithosphere, consistent with independent geochemical data. However, the lithospheric mantle is overall characterized by a highly heterogeneous thermochemical structure, with only some features correlating well with either Proterozoic and/or Cenozoic crustal structures. This suggests that most of the present‐day deep lithospheric architecture reflects the superposition of numerous geodynamic events of different scale and nature to those that created major crustal structures. This is consistent with the complex lithosphere‐asthenosphere system that we image, which exhibits a variety of multiscale feedback mechanisms (e.g., small‐scale convection, magmatic intrusion, delamination, etc.) driving surface processes. Our results also suggest that most of the present‐day elevation in the Colorado Plateau and surrounding regions is the result of thermochemical buoyancy sources within the lithosphere, with dynamic effects (from sublithospheric mantle flow) contributing only locally up to ∼15–35%. Key Points: We present a novel multiobservable probabilistic tomography method to image the thermochemical structure of the lithosphere and upper mantle We apply the new method to image study the lithosphere‐asthenosphere system beneath the Colorado Plateau and surrounding areas A complex and vigorous lithosphere‐asthenosphere system is imaged, with multiscale feedback mechanisms driving surface processes